Pre-fusion RSV F strongly boosts pre-fusion specific neutralizing responses in cattle pre-exposed to bovine RSV - Ann-Muriel Steff (Nature Portfolio, 2017)
Boosting of maternal antibodies against RSV is a potential approach to protect infants from severe infection, but data from animal models is missing. Here Steff et al. test two different boosts in seropositive cattle pre-exposed to bovine RSV and show that pre-fusion F strongly boosts neutralizing responses.